Home delivery among women who receive antenatal care in Ethiopia, design-based logistic regression analysis - Yimer Seid Yimer; Tariku Tesfaye; Awgichew Kifle Zemelak; Solomon Emyu Ferede (BMJ Public Health)
Background In Ethiopia, a significant proportion of women who receive antenatal care (ANC) deliver at home. This study aims to investigate home delivery among pregnant women who receive ANC during pregnancy in Ethiopia. Increased coverage of ANC is advised to improve institutional delivery, which in turn prevents maternal and neonatal morbidity and mortality.Patients and methods We used data from the Performance Monitoring for Action Ethiopia panel study, which followed pregnant women 1 year through post partum. A total of 1749 women who received ANC during pregnancy were included in this study. To identify risk factors associated with home delivery, a design-based binary logistic regression analysis was used.Results Of 1749 women who received ANC, 515 (29.4%) gave birth at home. Discussions on place of delivery with partner (adjusted OR (AOR)=0.56, 95% CI=0.35 to 0.90); desire to deliver at home (AOR=3.35, 95% CI=2.15 to 5.22); multiple birth readiness topics during ANC visits (AOR=0.39, 95% CI=0.21 to 0.63); and had ANC by a professional healthcare provider (AOR=0.40, 95% CI=0.23 to 0.70) were found to be significant predictors of home delivery.Conclusion This study found that one-third of women who received ANC gave birth at home. Discussions on place of delivery with partner, birth readiness topics, women’s desire for place of delivery and type of ANC provider were found to be independent predictors. Our results indicate for special attention to the evaluation and improvement of health extension workers’ competency in ANC delivery, and counselling women on various aspects of birth readiness during ANC visits.